Synthesis and characterization of surface-functionalized paramagnetic nanoparticles and their application to immobilization of α-acetolactate decarboxylase. Issue 9 (September 2015) - Qian, Siriguleng; Wang, Chun; Wang, Hongying; Yu, Fang; Zhang, Chunzhi; Yu, Hongshan
Graphical abstract: Schematic representation of synthesis of surface-functionalized PMN Fe3 O4 @SiO2 NH2 NPs (a) and its application to α -ALDC immobilization (b). Highlights: A facile paramagnetic nanoparticles (PMN Fe3 O4 @SiO2 NH2 NPs) have been synthesized. α -ALDC was immobilized onto the surface of PMN Fe3 O4 @SiO2 NH2 NPs using CDI as a covalent reagent. The immobilized α -ALDC had lower affinity to its substrate than the free α -ALDC. The immobilized α -ALDC revealed much better reusability during beer fermentation. Abstract: In this paper, a facile paramagnetic Fe3 O4 @SiO2 NH2 nanoparticles (PMN Fe3 O4 @SiO2 NH2 NPs) have been successfully synthesized and characterized, which were applied to α -acetolactate decarboxylase ( α -ALDC) immobilization using 1, 1′-carbonyldiimidazole (CDI) as the covalent reagent. The synthesized nanoparticles exhibited satisfactory paramagnetic under magnetic field, high single-crystalline and abundant amino groups on the surface. The α -ALDC loading capacity onto nanoparticles was 48.70 ± 1.25 μg/mg carrier and the activity of retained α -ALDC remained 69.39 ± 1.16% in comparison with free α -ALDC. Enzyme kinetics analysis showed that immobilized α -ALDC had lower affinity to its substrate than that of free α -ALDC based on higher K m and little lower V max of immobilized α -ALDC. After storage at 4 °C in disodium hydrogen phosphate and citric acid (DHPCA) buffer (20 mM, pH 6) for 14 days, immobilized α -ALDC retained 65.35% of its initial activity, while the activity of free α -ALDC only kept 39.22% in the same conditions. After 5 times re-use, immobilized α -ALDC still retained 31.03% of its initial activity for preventing diacetyl production.